SUFISM THE FOR MATIVE PERIOD - Ahmet T. Karamustafa (Edinburgh University Press, 2007)
Sufi sm, the major mystical tradition in Islam, emerged from within renunciatory modes of piety (zuhd) during a period that extended from the last decades of the second/eighth to the beginning of the fourth/tenth century. The earliest mystical approaches appeared in the fi rst half of this period, but these were likely disparate and heterogeneous in nature and, more signifi cantly, they remain obscure to modern researchers owing to sparse documentation. From the mid-third/ninth century onwards, however, Sufi s of Baghdad came into full view as members of a distinct mode of mystical piety. In the same time period, other mystical movements took shape elsewhere, notably in lower Iraq, northeastern Iran, and Central Asia. Mystics who belonged to these latter movements were not initially known as Sufi s, and in their thought and practice, they differed from Baghdad Sufi s and from each other in many ways, but they gradually blended with the Baghdad mystics, and in time, like them, they too came to be identifi ed as Sufi s.